(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this review article, we learned more about liposomes, a sort of drug delivery system utilised to target a specific tissue for the drug's effects. Liposomes can deliver medications where free medicines cannot because of the structural similarities between the lipid bilayer and the cell membrane. Because of its biocompatibility and capacity to encase hydrophobic molecules in the lipid domain, the liposomal delivery system has attracted attention as one of the noteworthy methods to improve dissolution and consequently absorption in the gastrointestinal (GI) tract. Due to its comparatively vast size, the GI tract's structural instability and low permeability across intestinal epithelia have been some of the disadvantages. In addition, despite the success of parenteral liposomes, there are yet to be any liposomal formulations authorised for oral use. However, the recent decade has seen a sharp rise in the number of published studies, which has led to a resurgence in liposomal oral administration. The majority of this research, however, has primarily involved in vitro tests, and there are not many water-insoluble medications that have in vivo evidence. People who are fairly new to this field of research should find the information in this article particularly useful.